Head and Neck Paragangliomas: Improved Tumor Detection Using Contrast-Enhanced 3D Time-of-Flight MR Angiography As Compared with Fat-Suppressed MR Imaging Techniques - van den Berg, René; Verbist, Berit M.; Mertens, Bart J. A.; van der Mey, Andel G. L.; van Buchem, Mark A. (American Journal of Neuroradiology, 2004)
BACKGROUND AND PURPOSE: MR imaging techniques have proved their efficacy in imaging the head and neck region. In this study, we compared T1-weighted, dual T2-weighted, and fat-suppressed MR imaging and unenhanced and contrast-enhanced 3D time-of-flight MR angiography sequences for detection of head and neck paragangliomas.METHODS: Thirty-one patients with 70 paragangliomas were examined. Four combinations of MR images were reviewed by two neuroradiologists: T1-weighted and dual T2-weighted fast spin-echo images, T1- and T2-weighted fat-suppressed fast spin-echo images, T1-weighted and contrast-enhanced T1-weighted fat-suppressed spin-echo images, and unenhanced and contrast-enhanced 3D time-of-flight MR angiograms. The randomized examinations were independently evaluated for image quality, presence of tumor, tumor size, and intratumoral flow signal intensity. The standard of reference for presence of tumor was digital subtraction angiography. Data were analyzed by using the logistic regression method.RESULTS: Mean sensitivity, specificity, and negative predictive values, respectively, were assessed by the two observers to be as follows: for dual T2-weighted fast spin-echo, 74%/99%/86%; for T2-weighted fat-suppressed fast spin-echo, 70%/100%/85%; for contrast-enhanced T1-weighted fat-suppressed spin-echo, 73%/100%/86%; and for unenhanced and contrast-enhanced 3D time-of-flight MR angiography, 89%/99%/93%. Sensitivity was significantly better for unenhanced and contrast-enhanced 3D time-of-flight MR angiography (P = .000028). More intratumoral flow signal intensity was depicted with unenhanced and contrast-enhanced 3D time-of-flight MR angiography.CONCLUSION: A combination of unenhanced and contrast-enhanced 3D time-of-flight MR angiography is superior for detecting paragangliomas and should be added to a standard imaging protocol, especially for patients with familial paragangliomas because they are more susceptible to multicentric disease.